Comparison of the effects of different foam rolling durations on knee extensors function - Kasahara, Kazuki; Konrad, Andreas; Yoshida, Riku; Murakami, Yuta; Koizumi, Ryoma; Thomas, Ewan; G Behm, David; Nakamura, Masatoshi (Biology of Sport, 2024)
Foam rolling (FR) intervention has recently attracted attention in sports and rehabilitation settings. However, the effects of FR using different rolling durations have not been fully clarified. Thus, this study focused on FR durations and examined the acute and prolonged (i.e., 20-min; 40-min, 60-min) effects of different FR intervention durations on maximal voluntary concentric contractions (MVC-CON), knee flexion range of motion (ROM), pain pressure threshold (PPT), and tissue hardness. The participants were 10 male university students (22.5 ± 1.0 years), and the target muscles were the dominant leg knee extensors. Three sets of 60-seconds FR interventions were performed in the randomized crossover trials in each condition. The three intervention conditions were fast (1 rolling/2 s, 30-repetition × 3 sets, 90 repetitions), medium (1 rolling/6 s, 10-repetition × 3 sets, 30 repetitions), and slow speed (1 rolling/12 s, 5-repetition × 3 sets, 15 repetitions). Before as well as immediately, 20-min, 40-min, and 60-min after the interventions, MVC-CON, ROM PPT, and tissue hardness were measured. The results showed no interaction effect in the acute effect but a main effect of time for all variables (p < 0.05). Also, no interaction was observed in prolonged effect, but main effects of time were observed in knee flexion ROM, PPT, and tissue hardness (p < 0.01) but not for MVC-CON. Post-hoc tests showed significant PPT (p < 0.05) and knee flexion ROM (p < 0.01) increases up to 20- and 60-minutes respectively after all interventions. Tissue hardness was significantly (p < 0.01) decreased up to 60-minutes after all interventions. This study showed that the FR intervention changed ROM, PPT, tissue hardness, and MVC-CON regardless of rolling duration and that the effects persisted up to 20–60 minutes.